PERSEPSI REMAJA MENGENAI POLA ASUH ORANG TUA DALAM MENDIDIK (Suatu Kajian di Jorong Lubuk Harto Kenagarian Koto Salak Kecamatan Koto Salak Kabupaten Dharmasraya) - -, Yusneli - (Bimbingan dan Konseling, 2014)
Background of this research is there are parents who do not pay attention teenagers education that cause the teenagers drop out school, the parents who pay less attention to teenagers interactions. This research aimed to describe: 1) Teenager perceptions toward parenting of democratic parents. 2) Teenager perceptions toward parenting of authoritarian parents. 3) Teenager perceptions toward parenting of laissez faire parents. This research was descriptive quantitative. The population of this research were the teenagers in Jorong Lubuk Harto Kenagarian Koto Salak Kecamatan Koto Salak Kabupaten Dharmasraya which were 40 people. In choosing the sample, the researcher used total sampling. The instrument was questionnaire. In addition, the researcher analyzed the data by using percentage formula. The results of this research showed that: 1) teenager perceptions about parenting of democratic parents were in good category. 2) teenager perceptions about parenting of authoritarian parents were in good category. 3) teenager perceptions about parenting of laissez faire parents were in good category.